3D and 4D printing of biomedical materials: current trends, challenges, and future outlook - Gayan A. Appuhamillage; Sankalya S. Ambagaspitiya; Rohan S. Dassanayake; Achintha Wijenayake (Open Exploration Publishing Inc., 2024)
Three-dimensional (3D) and four-dimensional (4D) printing have emerged as the next-generation fabrication technologies, covering a broad spectrum of areas, including construction, medicine, transportation, and textiles. 3D printing, also known as additive manufacturing (AM), allows the fabrication of complex structures with high precision via a layer-by-layer addition of various materials. On the other hand, 4D printing technology enables printing smart materials that can alter their shape, properties, and functions upon a stimulus, such as solvent, radiation, heat, pH, magnetism, current, pressure, and relative humidity (RH). Myriad of biomedical materials (BMMs) currently serve in many biomedical engineering fields aiding patients' needs and expanding their life-span. 3D printing of BMMs provides geometries that are impossible via conventional processing techniques, while 4D printing yields dynamic BMMs, which are intended to be in long-term contact with biological systems owing to their time-dependent stimuli responsiveness. This review comprehensively covers the most recent technological advances in 3D and 4D printing towards fabricating BMMs for tissue engineering, drug delivery, surgical and diagnostic tools, and implants and prosthetics. In addition, the challenges and gaps of 3D and 4D printed BMMs, along with their future outlook, are also extensively discussed. The current review also addresses the scarcity in the literature on the composition, properties, and performances of 3D and 4D printed BMMs in medical applications and their pros and cons. Moreover, the content presented would be immensely beneficial for material scientists, chemists, and engineers engaged in AM manufacturing and clinicians in the biomedical field.